Hot Gas Path Inspection (Hgpi) Of Gas Turbine Unit Type Ge Frame 9e An Documentary Study Involved the Steps of the (Hgpi) After 32k Running Hours of The Unit - Kadhim KASHI (Peerian Journals Publishing, 2024)
This paper details the Hot Gas Path Inspection (HGPI) procedure, a crucial periodic maintenance task for Frame-9E gas turbine units manufactured by General Electric. Regular HGPIs are essential for ensuring efficient and reliable operation of the turbines and preventing internal component damage. The HGPI process is divided into three main stages: disassembly, inspection, and reassembly. During disassembly, various components are meticulously removed, including the turbine roof, burners, combustion chambers, and turbine blades. A detailed inspection follows, focusing on parts designated for replacement and those generally left untouched during HGPI. Based on the inspection findings, necessary replacements are made, and components are thoroughly cleaned before reassembly. The reassembly stage involves meticulously reinstalling all previously removed components while adhering to strict measurements and specifications. Following the successful completion of HGPI and any related auxiliary system maintenance, the gas turbine unit is signed off as operational and ready to be handed over to the operations team
Keywords: Turbine; Iraq; GE Frame 9E; Replenishment Principle